2009
DOI: 10.1016/j.biocel.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A major cathepsin B protease from the liver fluke Fasciola hepatica has atypical active site features and a potential role in the digestive tract of newly excysted juvenile parasites

Abstract: The newly excysted juvenile (NEJ) stage of the Fasciola hepatica lifecycle occurs just prior to invasion into the wall of the gut of the host, rendering it an important target for drug development. The cathepsin B enzymes from NEJ flukes have recently been demonstrated to be crucial to invasion and migration by the parasite. Here we characterize one of the cathepsin B enzymes (recombinant FhcatB1) from NEJ flukes. FhcatB1 has biochemical properties distinct from mammalian cathepsin B enzymes, with an atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 74 publications
1
28
1
Order By: Relevance
“…Certainly, this task requires regulation at several levels and evolutionary, the parasite has achieved this through gene duplication, sequence divergence and selection of encoded proteases for better recognition of specific host proteins while at the same time selecting against protease isoforms with too high activity [4][5][6][7][8]. In addition, differential expression and release of unique sets of protease isoforms during development contribute to optimized activity levels at any given stage (for an overview see [2]).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Certainly, this task requires regulation at several levels and evolutionary, the parasite has achieved this through gene duplication, sequence divergence and selection of encoded proteases for better recognition of specific host proteins while at the same time selecting against protease isoforms with too high activity [4][5][6][7][8]. In addition, differential expression and release of unique sets of protease isoforms during development contribute to optimized activity levels at any given stage (for an overview see [2]).…”
Section: Introductionmentioning
confidence: 98%
“…Here we present data on a second type 1 cystatin in F. gigantica which suggests that it has an important function in the regulation of cathepsin B activity. In Fasciola distinct isoforms of cathepsin B have an unique role in the early infectious phase as determined by analysis of expression, substrate specificity and vaccine potential in recent years [4,[15][16][17] and the finding of a highly adapted inhibitor should be valuable for further analysis of the function of this protease and the development of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cathepsin B-selective inhibitor (CA-074) caused significant reductions of the motility and viability of F. hepatica NEJs (Beckham et al 2009). Biochemical study revealed that F. hepatica cathepsin B strongly reacted with substrates containing isoleucine or valine at the P2 position (Beckham et al 2009). This activity was different from most cathepsin Bs found in other species that preferentially cleaved substrates with leucine, phenylalanine, and arginine at the P2 position, suggesting that F. hepatica cathepsin B can be exploited as an anti-fluke drug target (Smooker et al 2010).…”
Section: Cathepsin Bmentioning
confidence: 98%
“…This may be due to the low identity of adult-specific cathepsin B1 compared to other juvenilespecific cathepsin Bs and, also, the low amount of cathepsin B expressed in the late juvenile and adult stages. In F. hepatica, the localization using a fluorescent-labeled active site probe detected active cathepsin B1 in the digestive tract of NEJs (Beckham et al 2009); however, its localization in the adult parasites has not been investigated.…”
Section: Cathepsin Bmentioning
confidence: 98%
See 1 more Smart Citation